Consistently low prevalence of syphilis among female sex workers in Jinan, China: findings from two consecutive respondent driven sampling surveys. - Meizhen Liao (PLoS ONE, 2012)
BACKGROUND: Routine surveillance using convenient sampling found low prevalence of HIV and syphilis among female sex workers in China. Two consecutive surveys using respondent driven sampling were conducted in 2008 and 2009 to examine the prevalence of HIV and syphilis among female sex workers in Jinan, China. METHODS: A face-to-face interview was conducted to collect demographic, behavioral and service utilization information using a structured questionnaire. Blood samples were drawn for serological tests of HIV-1 antibody and syphilis antibody. Respondent Driven Sampling Analysis Tool was used to generate population level estimates. RESULTS: In 2008 and in 2009, 363 and 432 subjects were recruited and surveyed respectively. Prevalence of syphilis was 2.8% in 2008 and 2.2% in 2009, while no HIV case was found in both years. Results are comparable to those from routine sentinel surveillance system in the city. Only 60.8% subjects in 2008 and 48.3% in 2009 reported a consistent condom use with clients during the past month. Over 50% subjects had not been covered by any HIV-related services in the past year, with only 15.6% subjects in 2008 and 13.1% in 2009 ever tested for HIV. CONCLUSIONS: Despite the low prevalence of syphilis and HIV, risk behaviors are common. Targeted interventions to promote the safe sex and utilization of existing intervention services are still needed to keep the epidemic from growing.